2018
DOI: 10.4103/ija.ija_488_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of landmark versus pre-procedural ultrasonography-assisted midline approach for identification of subarachnoid space in elective caesarean section: A randomised controlled trial

Abstract: Background and Aims:Identification of subarachnoid space in pregnant patients can pose a great challenge to anaesthesiologists. This study was designed to compare conventional landmark technique with pre-procedural ultrasonography-assisted midline approach for identification of the subarachnoid space in elective caesarean section.Methods:After institute ethics committee approval and written informed consent, 100 parturients scheduled for elective caesarean section under spinal anaesthesia were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Four articles involved 384 patients in the emergency room (ER) undergoing a lumbar puncture [ 20 , 21 , 22 , 23 ], while the remaining 28 articles involved 3031 patients undergoing neuraxial anesthesia. Nine studies examined 1169 patients undergoing epidural anesthesia [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], six studies examined 593 patients undergoing CSE anesthesia [ 33 , 34 , 35 , 36 , 37 , 38 ], and 13 studies examined 1293 patients who underwent spinal anesthesia [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Notably, 22 studies concerned obstetric patients.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles involved 384 patients in the emergency room (ER) undergoing a lumbar puncture [ 20 , 21 , 22 , 23 ], while the remaining 28 articles involved 3031 patients undergoing neuraxial anesthesia. Nine studies examined 1169 patients undergoing epidural anesthesia [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], six studies examined 593 patients undergoing CSE anesthesia [ 33 , 34 , 35 , 36 , 37 , 38 ], and 13 studies examined 1293 patients who underwent spinal anesthesia [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Notably, 22 studies concerned obstetric patients.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of successful dural puncture during the first needle insertion among the pre-procedural group was similar as in other studies. [ 7 8 9 ] This is an important finding since multiple attempts at needle placement are directly related to incidences of spinal haematoma, post-dural puncture headaches, and trauma to neural structures. Further, the number of needle passes required were also statistically less in the RUS group in comparison to the PUS group.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because it has been shown that the number of self-reported passes is always lower than the actual number of passes. [ 7 ] Third, the age of our population group was, on average, 59 years and spinal anaesthesia has been shown to be more difficult in older populations compared to the general adult population. [ 8 ] Fourth, we used a paramedian approach to the neuraxis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Dhanger et al .,[ 10 ] the time taken for the successful lumbar puncture was lesser in the preprocedural ultrasound group than in the traditional landmark group. In the present study, we found a similar decrease in the time taken for subarachnoid block in the ultrasound group than the landmark group.…”
Section: Discussionmentioning
confidence: 99%